2017
DOI: 10.14338/ijpt-17-00027.1
|View full text |Cite
|
Sign up to set email alerts
|

Proton Therapy Reduces Normal Tissue Dose in Extended-Field Pelvic Radiation for Endometrial Cancer

Abstract: Purpose: We dosimetrically compared pencil beam scanning (PBS) proton therapy and intensity-modulated radiation therapy (IMRT) for pelvic and para-aortic lymph node disease in endometrial carcinoma and present acute toxicities associated with extendedfield PBS. Patients and Methods: Twenty-five patients with locally advanced endometrial malignancies were enrolled in an image-guided registry study. Seven of these patients were treated with PBS, and 18 patients were treated with IMRT. Organs at risk included pel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…A small, prospective single-arm study by Lin et al evaluated 11 patients with gynecological cancer treated posthysterectomy and showed that pencil beam scanning (PBS) PT was able to reduce the dose to the OAR substantially compared to IMRT plans [26]. Xu et al demonstrated that PBS PT resulted in significantly lower volumes of exposed bone marrow, small bowel, and bladder when dosimetrically comparing PBS PT with IMRT for endometrial cancer [27]. An ongoing trial is the APROVE study, which is a prospective single-center one-arm study wherein 25 gynecological cancer patients with an indication for postoperative pelvic radiotherapy will be treated with PBS PT [38].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A small, prospective single-arm study by Lin et al evaluated 11 patients with gynecological cancer treated posthysterectomy and showed that pencil beam scanning (PBS) PT was able to reduce the dose to the OAR substantially compared to IMRT plans [26]. Xu et al demonstrated that PBS PT resulted in significantly lower volumes of exposed bone marrow, small bowel, and bladder when dosimetrically comparing PBS PT with IMRT for endometrial cancer [27]. An ongoing trial is the APROVE study, which is a prospective single-center one-arm study wherein 25 gynecological cancer patients with an indication for postoperative pelvic radiotherapy will be treated with PBS PT [38].…”
Section: Discussionmentioning
confidence: 99%
“…It should be investigated whether these lower OAR doses result in an actual toxicity reduction. Early studies demonstrated the feasibility of treating gynecological cancer patients with proton therapy [26,27]. Even though these results are encouraging, clinical data on our population of interest are sparse since these studies included only small groups of patients with diverse gynecological cancers and concurrent treatments.…”
Section: Introductionmentioning
confidence: 99%
“…Pencil beam scanning proton therapy showed reduced radiotherapy exposure to the pelvic bone marrow, small bowel, and large bowel. However, there was increased moderate- and high-dose exposure to the rectum, which reflects the posterior entry of the beams 15. For intact locally advanced cervical cancer, Marnitz et al compared intensity-modulated radiation, volumetric arc therapy, and proton therapy.…”
Section: Dosimetric Advantages Of Proton Therapymentioning
confidence: 99%
“…Modern treatment planning including intensity-modulated radiation has allowed for more comfortable treatment of these regions generally up to the level of renal vessels, and even dose escalation around the duodenum for gross nodal disease. 40 Our clinic has demonstrated the feasibility of using proton therapy for extended-field therapy in post-operative cancers 15 (Figure 3). Treatment of the para-aortic nodes with radiation is often employed in patients with early-stage testicular seminoma, and is feasible with proton therapy.…”
Section: Para-aortic Nodal Radiationmentioning
confidence: 99%
“…Gynecological-No referrals were submitted for gynecological cases during the month after the first case of COVID-19 in NYC, but our prioritization process recommends PBT for reirradiation gynecological cases [15] as well as cases requiring dose escalation for gross nodal disease in which OARs sparing cannot be adequately achieved with photon therapy. PBT without delay was also recommended for cases warranting extended field adjuvant radiation therapy, given superior dosimetry to photon radiation therapy [16], with the exception of , and node-positive prostate cancer were recommended to continue with and extend the duration of pre-radiotherapy androgen deprivation therapy with deferral of PBT treatment for at least 2 to 6 months [17]. 9.…”
Section: Recommendationsmentioning
confidence: 99%